TOLERANSI DAN MILITAN: POLITIK RELASI ANTARAGAMA SISWA MUSLIM KOTA PADANG - Andri Ashadi (UIN Sunan Kalijaga Yogyakarta, 2020)
Comfortable with people who different principles/religions and respecting these differences (tolerant), is often suspected of weakening one's religious commitment. Therefore, tolerance is often interpreted as simply allowing differences with all their uniqueness while refraining from all these uniqueness. Through surveys, in-depth interviews, analysis of Homi K. Bhabha's third space, and Frantz Fanon's theory of identity, especially towards Muslim students at Don Bosco Padang High School, this paper proves the opposite. These Muslim students who attend school in a predominantly Christian environment do show a fairly high tolerance, for example being willing to be part of diversity and to be empathetic. However, this coincides with the strengthening of militant attitudes such as seriousness in seeking religious knowledge even outside of school. Also their critical attitude towards school policies that do not accommodate Islamic values.